سرد الذات والسرد المضاد في رواية قناع بلون السماء لباسم خندقجي - فاطمة منـــاد; مريــم فــار; نعيمة بوغزالة امحمد (University of El-oued, 2025)
الملخص: تتناول هذه الدراسة ثنائية سرد الذات والسرد المضاد في رواية قناع بلون السماء لباسم خندقجي، بوصفها رواية فلسطينية أسيرة تنبني على كتابة الذات وتفكيك الخطاب الاستعماري. افتُتحت الدراسة بتأصيل نظري لمفهومي "سرد الذات" و"السرد المضاد"، باعتبارهما ركيزتين أساسيتين لفهم تمثلات الهوية والمقاومة في النص. ثم تم تحليل العتبات النصية: العنوان، الغلاف، الإهداء، والشعار، لما تحمله من دلالات تمهّد لتلقي الرواية في بعدها الذاتي والمقاوم. بعد ذلك، انتقلت الدراسة إلى تحليل الشخصيات ضمن محاور دقيقة: شخصية نور والأب، من خلال: التفكك الأسري، السلطة الأبوية، تقمّص الآخر،مقاومة الأب. شخصيات سماء، إسماعيل، ومراد، عبر: صورة الأسير الفلسطيني، سماء كمرآة لنور، ازدواجية الهوية. شخصيات أور وأيالا، ضمن: المرأة الجسد، الصراع الهوياتي والعرقي. أبرزت الدراسة كيف تتحول الذات الساردة في الرواية إلى ذات مقاومة، تستعيد صوتها وتؤسس سردًا مضادًا للهيمنة الصهيونية، استراتيجيات لغوية وسردية تُعيد بناء الهوية الفلسطينية من داخل الأسر. Résumé :فرنسية أو انجلزية This study explores the duality of self-narration and counter-narration in A Mask the Color of the Sky by BassimKhandaqji, a Palestinian prison novel grounded in self-writing and the deconstruction of colonial discourse. It begins with a theoretical framing of both concepts as essential tools for understanding identity and resistance representations in the text. The study then analyzes the paratextual elements—title, cover, dedication, and motto—as signifiers that shape the reader's reception of the novel’s personal and resistant dimensions. Character analysis is structured around the following axes: Noor and his father: family disintegration, paternal authority, embodying the Other, resisting the father. Samaa, Ismail, and Murad: image of the Palestinian prisoner, Samaa as Noor’s mirror, identity duality. Or and Ayala: woman as body, ethnic and identity conflict. The study concludes that the narrative voice evolves into a voice of resistance, reconstructing Palestinian identity through counter-discursive strategies, restoring the captive individual’s ability to speak, write, and resist..
مذكرة .ماستر . أدب حديث ومعاصر. 2025
Keywords: سرد الذات، السرد المضاد، قناع بلون السماء، باسم خندقجي; Self-narrative; counter-narrative; The Mask the Color of the Sky; Bassem Khandakji